2023
DOI: 10.1111/ppl.14038
|View full text |Cite
|
Sign up to set email alerts
|

Response of exogenous melatonin on transcription and metabolism of soybean under drought stress

Liang Cao,
Jingnan Zou,
Bin Qin
et al.

Abstract: Amino acid metabolism is an important factor in regulating nitrogen source assimilation and source/sink transport in soybean. Melatonin can improve plant stress resistance, but whether it affects amino acid metabolism is not known. Therefore, this study investigated whether exogenous melatonin had an effect on amino acid metabolism of soybean under drought conditions and explored its relationship with yield. The treatments were normal water supply treatment (WW), drought stress treatment (D), drought stress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Glutamate synthase (GOGAT), nitrate reductase (NR), and glutamate dehydrogenase (GDH) are key enzymes in crop nitrogen metabolism that help crops cope with drought stress; their activities fully reflect the level of nitrogen assimilation in the crop 6 8 . Cao et al 9 found that the activity of NR was inhibited under drought stress. Xu et al 10 reported that drought stress reduces NR and GS activity in soybean leaves, and the GOGAT activity shows a trend of initially increasing and then decreasing.…”
Section: Introductionmentioning
confidence: 99%
“…Glutamate synthase (GOGAT), nitrate reductase (NR), and glutamate dehydrogenase (GDH) are key enzymes in crop nitrogen metabolism that help crops cope with drought stress; their activities fully reflect the level of nitrogen assimilation in the crop 6 8 . Cao et al 9 found that the activity of NR was inhibited under drought stress. Xu et al 10 reported that drought stress reduces NR and GS activity in soybean leaves, and the GOGAT activity shows a trend of initially increasing and then decreasing.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin (chemical name: N-acetyl-5-methoxytryptamine, MT, or Mel) is a versatile small molecule compound belonging to the indole heterocyclic group [ 9 ]. Numerous studies have demonstrated that melatonin is involved in various physiological processes, including alleviating the inhibition of photosynthesis, promoting seed germination, regulating plant growth and root morphology [ 10 , 11 , 12 , 13 , 14 ], and regulating primary and secondary metabolism [ 15 , 16 ]. Under water deficit conditions, exogenous melatonin increased the expression of important genes such as superoxide dismutase (SOD), peroxidase (POD), and phenylalanine ammonia-lyase (PAL) in hickory ( Carya cathayensis ) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%